Paternal and maternal genetic analysis of a desert Keriyan population: Keriyans are not the descendants of Guge Tibetans. - Kaixu Chen; Abdurahman Ablimit; Fengjun Ling; Weiwei Wu; Wenjuan Shan; Wenbei Qin; Tuerhong Keweier; Hongli Zuo; Fuchun Zhang; Zhenghai Ma; Xiufen Zheng (PLoS ONE, 2014)
The Keriyan people live in an isolated village in the Taklimakan Desert in Xinjiang, Western China. The origin and migration of the Keriyans remains unclear. We studied paternal and maternal genetic variance through typing Y-STR loci and sequencing the complete control region of the mtDNA and compared them with other adjacent populations. Data show that the Keriyan have relatively low genetic diversity on both the paternal and maternal lineages and possess both European and Asian specific haplogroups, indicating Keriyan is an admixture population of West and East. There is a gender-bias in the extent of contribution from Europe vs. Asia to the Keriyan gene pool. Keriyans have more genetic affinity to Uyghurs than to Tibetans. The Keriyan are not the descendants of the Guge Tibetans.